A EFICÁCIA DOS DIREITOS FUNDAMENTAIS E A IRRADIAÇÃO DOS PRINCÍPIOS CONSTITUCIONAIS SOBRE O DIREITO CIVIL (Reflection and Critique Law Magazine, 2022)
Facing the tension between the possibility or not of reading the private law institutes in a constitutional perspective, through the irradiation of constitutional principles, this study looks for possible answers within the theory of fundamental rights. For this, a theoretical survey of the main concepts of fundamental law, rule, order and principle will be made, so that it is possible to identify keys of readings capable of harmonizing, within the constitutional theory, the dialogue between the orders. Already recognizing that, if, on the one hand, it neglects to deny the imperative of constitutional rules, on the other, the constitutional interest frustrates the unrestricted application of its principles. Thus, the article will seek a middle ground capable of answering these questions.